The Influence of Three-Dimensional Visualization Media on Spatial Skills and Creative Thinking of Elementary School Students - Disman; Gunawan (Desimal: Jurnal Matematika, 2026)
This study investigated the influence of three-dimensional visualization media on elementary school students’ spatial ability and creative thinking in geometry learning. The study was grounded in students’ persistent difficulties in interpreting solid figures, recognizing object viewpoints, and transforming spatial representations when geometry is taught through conventional explanation and static images. A quantitative quasi-experimental design with a non-equivalent control group pretest-posttest model was employed. The participants were 50 sixth-grade students from two public elementary schools in Karangpucung District, Cilacap Regency, Indonesia, consisting of 27 students in the experimental class and 23 students in the control class. The experimental class learned cubes, cuboids, and composite spatial structures using three-dimensional visualization media, whereas the control class received conventional instruction. Data were collected using spatial ability and creative thinking tests and analyzed through descriptive statistics, Shapiro-Wilk normality testing, Levene’s homogeneity testing, independent samples t-test, and Pearson correlation. The results showed that the experimental class achieved significantly higher outcomes than the control class in spatial ability, t(48) = 4.514, p < .001, and creative thinking, t(48) = 7.816, p < .001. A strong positive correlation was also found between spatial ability and creative thinking, r = .756, p < .001, indicating that students with stronger spatial reasoning tended to demonstrate stronger creative mathematical thinking. These findings suggest that three-dimensional visualization media function as cognitive scaffolds that support visual-spatial representation, mental transformation, and flexible idea generation. The study contributes to technology-enhanced geometry learning by demonstrating that interactive visual media can simultaneously strengthen spatial reasoning and creative thinking in elementary mathematics education.